Photochemical reaction mechanisms and kinetics with molecular nanocrystals: surface quenching of triplet benzophenone nanocrystals - Simoncelli, Sabrina (2010)
Organic molecular nanocrystals suspended in water are useful when studying reactions that occur in the solid state because they retain not only the reactive and supramolecular properties of bulk crystals, but are also amenable to transmission spectroscopy. Having previously studied the triplet state of benzophenone nanocrystals by laser flash photolysis transmission spectroscopy, we now report nanosecond experiments in the presence of several possible quenchers: anionic and cationic surfactants, dissolved oxygen, and as a function of solvent deuteration (H2O and D2O). After finding these to have no effect, several anionic quenchers (IS, BrS, and NS3) were tested by Stern-Volmer analysis. Significant correlation between the quenching rates in solution and in nanocrystals suggests that the electronic excitation is accessible to quenchers at the surface. © 2010 John Wiley & Sons, Ltd.